Optimization of Drying Conditions for Quality Dried Tomato Slices Using Response Surface Methodology. Issue 3 (11th December 2012) - Abano, E.E.; Ma, H.; Qu, W.
Abstract The response surface method was used to investigate the results of experiment designed with the Box‐Behken approach to make known the effects of air temperature, air velocity and sample thickness, on drying time, lycopene content, ascorbic acid content, non‐enzymatic browning and color of dried tomato slices. Three levels of temperature (40 to 60C), air velocity (1.0 to 2.0 m/s) and sample thickness (7 to 11 mm) were used for the experiment. The desirability index technique was used to predict the ideal drying condition. At the best conditions of 44C air temperature, 2.0 m/s air velocity and 7.72 mm sample thickness, drying time was 527 ± 76 min, lycopene content was 62.7 ± 4.3 mg/100 g dry matter, ascorbic acid content was 3.07 ± 0.14 mg/g dry matter, brightness value was 62.92 ± 2.18, ratio of redness to yellowness was, 0.78 ± 0.05 and the non‐enzymatic browning index was 0.55 ± 0.06 absorbance unit. Practical Applications The research took practical desires of minimum drying time and non‐enzymatic browning and maximum values of lycopene content, ascorbic acid, color brightness and redness to yellowness ratio into consideration. These quality indicators are of topmost importance to the food industries involved in tomato drying. The quality of dried products obtained using response surface methodology provides industries with optimized conditions for improving the quality of dried tomatoes. The dried product is a valuable ingredient in the preparation ready to enjoy soups, sauces and pizzas.